Outcome-Based Introduction to English Linguistics Course: The Perspectives of Indonesian EFL Leaners - moch. saiful islam (EDUCAFL : Journal of Education of English as Foreign Language, 2023)
AbstractThis study aims to evaluate the implementation of Outcome Based Education (OBE) in Introduction to English Linguistics course based on students perspectives. A total of 143 students of English Language Education Study Program Brawijaya University participated for this study. Two parts questionnaires from Lixun (2013) adopted as the instrument for this study. The result showed the students positives responses towards teaching and learning activities in supporting their learning outcomes. Meanwhile, the finding relates to the students self confidence towards their learning outcomes showed unsatisfactory result. An in depth study towards students self confidence in achieving learning outcomes is needed to be conducted in the future.Keywords: Outcome Based Education, Introduction to English Linguistics; Students Perspectives